Super-leveling, fraying-out, internal restructuring: A century of present be concord in Tristan da Cunha English. (17th June 2016) - Schreier, Daniel
ABSTRACT: The present study analyzes present be leveling with pivot is (as in I is, we is, the old dogs is ) in Tristan da Cunha English, a variety of South Atlantic English that developed in geographic isolation and under intense contact conditions. The findings, based on data from a total of 45 speakers born throughout the 20th century, indicate that community-wide variation correlates with social history; whereas present be was subject to (near-)categorical leveling until the 1940s, an opening-up phase after World War II saw interaction with speakers of other dialects on the island, which triggered an increase of a standard am/is/are concord pattern. Variability began to increase from the 1950s onward and the community has now frayed out widely in its usage of leveled is forms (ranging from 10% to over 90% in speakers of the youngest generation, born in the 1980s). The internal constraint ranking for preceding environment in younger generations was partially restructured, which suggests that the social changes affected the grammatical variable. Three outliers represent exonormative orientation and outward mobility.